Physicochemical properties and sensory attributes of nut-based milk coffee - Woorin Lee; Hyunwoo Ahn; Jonggab Yim; Yuri Kim; Kwang-Geun Lee (Scientific Reports)
Abstract Since the use of animal-based milk raises environmental concerns and health issues such as allergies and lactose intolerance, the demand for plant-based milk alternatives is growing. This study aimed to (1) develop nut-based milks—almond, cashew, hazelnut, and walnut—combined with Arabica espresso and (2) assess their physicochemical and sensory qualities. Oleic, linoleic, and linolenic acids increased significantly in roasted nut-based milk coffees (p < 0.05). Particle size and viscosity were higher in nut-based coffees than in commercial milk (p < 0.05). Gas chromatography identified 33 volatile compounds; the nut-based milk coffee sample contained more benzaldehyde and 1-methylpyrrole-2-carboxaldehyde, while commercial milk coffee had higher 5-methyl furfural and furfuryl alcohol (p < 0.05). Sensory testing showed a preference for cashew nut-based milk coffee (p < 0.05). Vegan coffee produced with nut-based milks exhibited higher antioxidant activity and a higher unsaturated fatty acid content than those prepared with commercial milk. In particular, the roasted nut-based milks displayed increased levels of these beneficial compounds. These results offer insights into nut-based milk coffee’s physicochemical and sensory characteristics and preference factors.